Implementation of the Recitation of Rotibul Athos at the Manba'ul Qur'an Zahidiyah Islamic Boarding School for the Study of the Qur'an - Ridho Nur Hidayah; Lailatun Nihayati; Tafaul Fatma Nur Azizah; Dwi Aminatus Sa’adah (Aslim: Journal of Education and Islamic Studies, 2025)
This research aims to delve deeper into the practice of reciting Rotibul Athos in Islamic boarding schools (pesantren), a spiritual tradition that remains preserved to this day. Rotibul Athos is a series of prayers and dhikr (remembrance of God) composed by Sufi scholars intended to draw closer to Allah SWT, seek protection, and strengthen the spiritual bonds of Muslims. In the context of Islamic boarding schools, reciting Rotibul Athos is an integral part of the students' routine worship and religious learning process. This tradition holds strong spiritual, social, cultural, and educational values, shaping the students' character and personality. This research employed a qualitative method with a phenomenological approach, conducted at a traditional Islamic boarding school located in the Klutuk village, Tambakboyo District, Tuban Regency, East Java. Information was obtained through in-depth interviews with the caretaker, ustadz (teacher), and students, as well as direct observation of the Rotibul Athos recitation activity and the collection of related documents. Data analysis was conducted using descriptive thematic methods to identify the meaning, value, and impact of these activities on the students' lives. The research results indicate that reciting Rotibul Athos serves several important roles: as a spiritual tool to strengthen faith and piety, as a medium for building discipline and togetherness among students, and as an effort to maintain religious traditions deeply rooted in Islamic boarding school culture. This collective dhikr activity also has a positive impact on the character development of students, particularly in terms of sincerity, patience, obedience, and a sense of responsibility towards others. Students who regularly recite Rotibul Athos tend to experience greater peace of mind and demonstrate stable religious behavior in their daily lives. It is hoped that the results of this research will contribute to the study of Islamic spirituality in Islamic boarding schools and serve as a reference for other Islamic educational institutions in preserving religious traditions rich in values.